Revising the taxonomy of Darevskia valentini (Boettger, 1892) and Darevskia rudis (Bedriaga, 1886) (Squamata, Lacertidae): a Morpho-Phylogenetic integrated study in a complex Anatolian scenario - Arribas, Oscar; Candan, Kami̇l; Kornilios, Panagiotis; Ayaz, Di̇nçer; Kumlutaş, Yusuf; Gül, Serkan; Yilmaz, Can; Caynak, Eli̇f Yildirim; Ilgaz, Çeti̇n (Zootaxa, 2022)
Revealing biodiversity allows the accurate determination of the underlying causes of many biological processes such as speciation and hybridization. These processes contain many complex patterns, especially in areas with high species diversity. As two of the prominent zoogeographic areas, Anatolia and Caucasus are also home to the genus Darevskia, which has a complex morphological structure and parthenogenetic speciation. Darevskia valentini and D. rudis are two largely distributed taxa of this genus, both of which have a controversial taxonomic delimitation. Here we performed both a highly detailed morphological comparison and a molecular evaluation for the populations in both species groups. The most comprehensive taxonomic revision of this complex was carried out to determine the cases where the data obtained were compatible or not with each approach. As a result of the obtained outputs, it seems that D. spitzenbergerae stat. nov., D. mirabilis stat. nov. and D. obscura stat. nov. should be accepted as the species level, this later with subspecies D. o. bischoffi comb. nov. and D. o. macromaculata comb. nov.. Also, we propose two new taxa: D. josefschmidtleri sp. nov. and D. spitzenbergerae wernermayeri ssp. nov.. It has also been shown that “lantzicyreni” subspecies belong to D. rudis instead of D. valentini. The extensive revision has contributed to subsequent studies to more accurately understand the past histories of species in the genus Darevskia.